IDENTIFIKASI BEBERAPA SPESIES RUMPUT LAUT YANG POTENSIAL DIBUDIDAYAKAN DI PERAIRAN SULAWESI SELATAN (Torani Journal of Fisheries and Marine Science, 2017)
Indonesia has a long costline dan have a high natural fisheries resources. One of natural resources from thecoast area is seaweed. Seaweed is export commudity from fisheries sector and Indonesia is one of the thirdmain producer for seaweed in the world. Seaweed species that have been cultured and utilized was onlyseveral species such as Glacillaria sp, Euchema cottoni and Geledium sp, on the other hand, Indonesia has ahigh diversity of seaweed. Based on LIPI data survey on 1998, it was found that 55 species of seaweed atIndonesian waters. Through this data, it showed that Indonesian water has a high potency for seaweedculture development. Aims of this study were to identify seaweed species that has a high potency to becultured at South Sulawesi’s waters and to analyse natural potency of several seaweed species that can becultured. Results study showed that diversity of seaweed species was varied within South Sulawesi’s waters.The highest number of species account for 30 species that found at Pangkep waters and the lowest number ofspecies was found at Bone waters account for 5 species. There were three class of seaweed that found fromlocations, such as Red, Brown and Green algae. The highest number of species from Red algae class wasfound from Bantaeng waters, furthermore the highest number of species from brown algae class was foundfrom Pangkep waters.Keywords : Seaweed, seaweed culture, South Sulawesi waters.